Efektifitas Kerja Kepala Sekolah dengan Gaya Kepemimpinan Kharismatik - Agus Fahmi (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2020)
A successful school principal is not a born principal, destined to become a principal, but he can become a principal based on a planned and mature formation (special education or experience working as a teacher and principal), and willing to shape himself into a head quality school. The formulation of the problem in this study aims to determine the relationship between the principal's charismatic leadership and the work ethic of the teacher and to determine the level of charismatic leadership in school heads and the work ethic of teachers in SMKN 1 Kuripan, district. West Lombok. This type of research is quantitative research, the population of this research is teachers at SMK Negeri 1 Kuripan, district. West Lombok, amounting to 56 teachers. Because the number of the study population is relatively small, therefore this study is a population study of 56 teachers. The instrument used was a closed questionnaire. There was a statistical data analysis used in this study using the Product Moment correlation formula. The results showed that the value (calculated) was 0.538 or greater than the r-table value of 0.218 so that the decision to take was to accept the alternative hypothesis (Ha). This means that there is a "significant" positive relationship between the charismatic leadership of the school and the work ethic of the West Lombok SMKN 1 Kuripan teachers for the 2019/2020 academic year.  Keywords: Work effectiveness, Charismatic Leadership